2022
DOI: 10.3389/fnut.2022.827630
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Appetite-Dependent Hormones and Body Composition After 8 Weeks of High-Intensity Interval Training and Vitamin D Supplementation in Sedentary Overweight Men

Abstract: Exercise and diet are important factors for energy balance and appetite regulation. The aim of this study was to investigate the effect of 8 weeks High Intensity Interval Training (HIIT) and vitamin D3 supplementation in sedentary overweight men. Forty-eight participants were randomly assigned to one of the following four groups (n = 12): HIIT + VitD, HIIT + placebo (3 sessions per week, 10 × 1 min interval cycling at 90–100% VO2peak separated by 1 min active recovery at 15% VO2peakfor 8 weeks), Vit D and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…However, our results are in line with previous studies regarding interventions comprising either increased physical activity/exercise or combinations of exercise and dietary advice (but excluding very-low-energy diets). These studies have reported unaltered levels or even increased PYY and CCK levels as well as decreased GIP levels ( Jones et al, 2009 ; Vos et al, 2011 ; Guelfi et al, 2013 ; Martins et al, 2013 ; Lean and Malkova, 2016 ; Sheikholeslami-Vatani and Rostamzadeh, 2022 ). Here, it must be noted that weight loss in these studies was, as in our study, modest or not apparent and results are not completely consistent ( Lien et al, 2009 ; Lean and Malkova, 2016 ; Ataeinosrat et al, 2022 ; Sheikholeslami-Vatani and Rostamzadeh, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our results are in line with previous studies regarding interventions comprising either increased physical activity/exercise or combinations of exercise and dietary advice (but excluding very-low-energy diets). These studies have reported unaltered levels or even increased PYY and CCK levels as well as decreased GIP levels ( Jones et al, 2009 ; Vos et al, 2011 ; Guelfi et al, 2013 ; Martins et al, 2013 ; Lean and Malkova, 2016 ; Sheikholeslami-Vatani and Rostamzadeh, 2022 ). Here, it must be noted that weight loss in these studies was, as in our study, modest or not apparent and results are not completely consistent ( Lien et al, 2009 ; Lean and Malkova, 2016 ; Ataeinosrat et al, 2022 ; Sheikholeslami-Vatani and Rostamzadeh, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported unaltered levels or even increased PYY and CCK levels as well as decreased GIP levels (Jones et al, 2009;Vos et al, 2011;Guelfi et al, 2013;Martins et al, 2013;Lean and Malkova, 2016;Sheikholeslami-Vatani and Rostamzadeh, 2022). Here, it must be noted that weight loss in these studies was, as in our study, modest or not apparent and results are not completely consistent (Lien et al, 2009;Lean and Malkova, 2016;Ataeinosrat et al, 2022;Sheikholeslami-Vatani and Rostamzadeh, 2022). Thus, whether this (potentially beneficial) lack of strong hormonal alterations is due to the mode or the amount of weight loss/fat mass decrease, we cannot determine here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the analysed scientific articles demonstrated statistically significant effects of HIIT and DS on BF and induced a reduction of %FAT, body fat mass, BMI, or waist-to-hip ratio [32,33,36,[39][40][41][42][43][44]. On the contrary, two investigations [35,37] did not find any effects of HIIT combined with DS on BF in older adults with overweight and obesity.…”
Section: Effects Of Hiit Combined With Supplementation On Bfmentioning
confidence: 93%
“…Among different HIIT protocols, the 40-m shuttle run test was implemented most frequently [33,34,36,38,41] and was combined with ginger (3000 mg/daily) [33,34] or green tea supplementation [36,38], which proved to be effective in reducing BF of participants with overweight and obesity to a greater extent than HIIT or DS alone [33,36,38]. Conversely, Sheikholeslami-Vatani et al [41] found that the 40-m shuttle run protocol combined with vitamin D 3 (2000 IU/daily) or placebo supplementation both had a similar effect on the indicators of body fat loss: %FAT, BM and BMI, whereas Saghebjoo et al [37] demonstrated that the 40-m shuttle run HIIT combined with L-arginine (6 g/daily) did not cause a significant reduction of the BF mass. The above-mentioned synthesis of the results allowed us to conclude that a 40-m shuttle run test as a HIIT protocol may be effective in inducing BF loss both alone and in combination with DS, especially with green tea.…”
Section: Hiit: the Most Popular Protocolmentioning
confidence: 99%